Balanced Scorecard as strategic management and performance in PT. Fajar Surya - Lukmansyah Rifai Amirudin*; Rahmat Farulian (Riwayat: Educational Journal of History and Humanities, 2023)
This study aims to measure the company's performance and see the opportunities and challenges that exist outside the company in order to obtain alternative strategies to achieve company goals. Researchers measure the performance of PT. Fajar Surya by looking at the actual achievements of the company's important indicators. The indicators used are the perspective of finance, customers, internal business processes, growth, and learning combined with the external side of the company through the TOWS analysis method. This is an update (novelty) from previous studies that only used the BSC concept. The results of the research show that there are several strengths and weaknesses as well as opportunities and challenges that can be formulated to become alternative strategies. This research is expected to provide input regarding a comprehensive performance appraisal system for companies and additional empirical evidence regarding the concept of performance measurement with a combination of BSC and TOWS.